ISLAMIC CORPORATE CULTURE MODEL FOR ISLAMIC BANKING - Anis Byarwati (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2016)
Islamic Banking is designed to implement Islamic values in the fields of finance and banking. Therefore, the excellence of Islamic banks is not only determined by the things that are visible (tangible), such as management,-provided facilities, organizational structure, but also by the things that are invisible (intangible), such as the extent to the which the value of Islamic values are implemented in it, and how strong reviews those values are embedded into the corporate culture. Corporate culture has a strong influence on the behavior of all employees, Thus, it is also influential in affecting the firm performance (Kotter and Heskett, 1992; Schermerhornet al, 1997; Moeldjono, 2005; Robbins and Judge, 2007; Byarwati, 2007). This study aims to create an alternative to the model for the Islamic Corporate Culture of Islamic banking. By using a qualitative approach through analysis and synthesis concepts of Islam in the areas of management, this study successfully formulates an alternative to the model of Islamic Corporate Culture for Islamic banking.Keywords: Islamic Banking, Islamic Corporate Culture, Islamic values, Qualitative Approach, Management.